Neural substrates associated with irrelevant information suppression in problem-solving: an fMRI study of the Remote Associates Test - Ohkuma, Reiji; Kurihara, Yuto; Osu, Rieko (Frontiers in Human Neuroscience, 2025)
Suppressing irrelevant information during problem-solving is vital. Misleading or unrelated information may hinder the performance. However, previous studies inferred suppression-related brain regions based on overall problem-solving or pre-solution neural activity, resulting in insufficient experimental control over the precise timing of suppression and the types of information requiring suppression. In this study, we presented different types of distractors when introducing a problem to examine neural activity associated with suppressing unnecessary information. Participants completed the Japanese version of the Remote Associates Test in an MRI scanner under three conditions: strongly misleading, weakly related, and no distractors. Before the experiment, the participants were informed about the distractors and instructed to ignore them when the problem was presented. The findings showed that stronger suppression demands at problem onset increased the activation of the bilateral inferior frontal gyrus (IFG). Furthermore, the IFG activity, initiated at the beginning of the problem, decreased gradually rather than toward obtaining a solution to the presented problem. These findings suggest that the bilateral IFG supports problem-solving by suppressing irrelevant information.